The Relationship between Family Income and Maronutrient Intake with the Incidence of Chronic Energy Deficiency in Pregnant Women - Siti Raodah; Suminah Suminah; Revi Gamma Hata Novika (Indonesian Journal of Global Health Research, 2026)
Chronic Energy Deficiency (CED) in pregnant women remains a major public health problem in developing countries, including indonesian. Socioeconomic factors such as family income and inadequate macronutrient intake play an important role in the occurrence of CED.  This study aimed to analyse the relationship betwen family income and macronutrient intake with the incident of chronic enegry deficiency in pregnant women. This study employed an observational analytic design with cross-sectional apporach. The study population consisted of pregnant women who attended antenatal care service at primary health centres. Family income data were collected using structured questionnaires, while amcronutrient intake (enegry, protein, fat and carbohydrate) was assessed using a 24-hour dietary recall. The incidence of CED was determined based on MUAC measurement. Data were analysed using appopriate statistical test with a significance level of 0.05. The result showed the signicant relationship between family income and the incidence of chronic energy deficiency in pregnant women (p<0.05). in addition, inadequate macronutrient intake, particularly enegry and protein intake, was significantly associated with the incident of CED (p<0.05). family income and macronutrient intake are significantly associated with the incident of chronic energy deficiency in pregnant women. Effort to impove household economic conditions and maternal mutritional intake are essential to prevent CED during pregnancy.